Wirelessly powered dielectrophoresis of metal oxide particles using spark‐gap Tesla coil. Issue 24 (21st October 2020) - Budiman, Faisal; Silalahi, Desri Kristina; Muhamad, Bagaskoro; Fathurahman, Muhammad Rafi; Rozana, Monna; Tanaka, Hirofumi
Abstract: Wirelessly powered dielectrophoresis (DEP) of metal oxide particles was performed using a spark‐gap Tesla coil (TC). The main contribution of this work is the simplification of the conventional DEP setup that requires attaching wires directly to the electrodes. Wireless power from the TC generates a high output frequency and voltage, which corresponds to that used for the DEP. Therefore, a spark‐gap TC was built and utilized to conduct the DEP process. Metal oxides (ZnO and Fe2 O3 ) were used as targets for the assembly. The results showed that the wirelessly powered DEP technique via a TC was successful in assembling the metal oxide particles. Positive and negative DEP phenomena were observed. Positive DEP occurred during ZnO assembly, making particles chain grow 0.92 mm toward the sparks within 60 s. Negative DEP was observed during Fe2 O3 assembly, where the repulsion of particles formed a void around the sparks with a 1.45 mm radius. The mechanism of this wireless DEP system is discussed.